What Kind of Citizen? The Politics of Educating for Democracy - Westheimer, Joel; Kahne, Joseph (American Educational Research Journal, 2004)
Educators and policymakers increasingly pursue programs that aim to strengthen democracy through civic education, service learning, and other pedagogies. Their underlying beliefs, however, differ. This article calls attention to the spectrum of ideas about what good citizenship is and what good citizens do that are embodied in democratic education programs. It offers analyses of a 2-year study of educational programs in the United States that aimed to promote democracy. Drawing on democratic theory and on findings from their study, the authors detail three conceptions of the “good” citizen—personally responsible, participatory, and justice oriented—that underscore political implications of education for democracy. The article demonstrates that the narrow and often ideologically conservative conception of citizenship embedded in many current efforts at teaching for democracy reflects not arbitrary choices but, rather, political choices with political consequences.